PENGARUH INKLUSI FASA-211 TERHADAP SIFAT LISTRIK SUPERKONDUKTOR YBa2Cu3O7-x. - Sukirman, E.; Adi, W. Ari; Winatapura, D. S.; Yustinus, Yustinus (MESIN, 2006)
Effect of the211-phase inclusion to the electrical properties ofYBa2Cu307.x superconductor grown bya melt-texturing process has been investigated. The qualitative andquantitative analysis was carried out bythe x-ray diffraction technique using the Rietveld methode andthe electrical properties were investigated bythefour pointprobe methode. The analysisresults showthat the highestcritical current density was obtainedon the 123-phase matrix containing 35 weight%ofthe211-phase. Due to the 211-inclusion in the 123-phase,thefluxflow phenomenon does not longer exist. The criticalcurrent Jc in the 123-phase increaseon accountofthe 211-inclusion, where as the Jc tend to increae with increasing the 211-phase content. The further of211-phaseincrease, however, lead to a decreaseofJc value.